Effectiveness of Child to Parent Communication Using Information Package on Food Hygiene - Bhutia, Ms. Sonam Yangchen; Saini, Dr. Sushma Kumari; Kaur, Dr. Manmeet; Ghai, Dr. Sandhya (International Journal of Innovative Research in Medical Science, 2018)
School children can act as change agent not only for families but for community. The study aimed to assess effectiveness of information package on knowledge and practices of parents/family members of school children studying in Govt. Sr. Sec. School on food hygiene in Dhanas and Daddu Majra Colony, UT, Chandigarh. A non-randomised controlled trial was conducted on 201 school children studying in VIIth standard and their parents/family members. Purposive sampling technique was utilised to enrol 101 in case and 100 participants in control group. Interview schedule for knowledge assessment and observation checklist for assessing the practices of parents/ family members was used. Pre assessment of both the groups was done by a home visit. Experimental group school children were educated on food hygiene as per the protocol. Pre and post-test knowledge of school children on food hygiene was assessed and were asked to disseminate the information to their parents/family members. After 15 days, second time home visit was done to the parents/family members of both the groups for the post assessment of knowledge and practices. Significant improvement in knowledge and practices of parents/family members related to food hygiene was observed. Hence, school children can be an effective tool in health related knowledge dissemination which can further promote healthy practices.